Permanent magnet material with low eddy current loss
By introducing specific proportional elements and coordinated grain boundary diffusion materials into Nd-Fe-B magnets, and adopting hydrogen breaking and dehydrogenation processes, the eddy current loss is successfully reduced, the performance and efficiency of the magnets are improved, and the problem of large eddy current loss of rare earth permanent magnet materials in high-frequency environments is solved.
Patent Information
- Application Number
- CN202510108110.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Rare earth permanent magnet materials are prone to eddy currents in high-frequency alternating electric field environments, resulting in a decrease in magnetic properties and heat heating. It is difficult for the prior art to effectively reduce eddy current losses.
By introducing the ratio of PrNd, Dy, Fe, B and M elements into the Nd-Fe-B magnet, and using the synergistic grain boundary diffusion material TbxAlyCuz, combined with hydrogen breaking and dehydrogenation processes, a multi-step process is carried out to prepare a permanent magnet material with low eddy current loss.
It significantly reduces eddy current loss, improves the coercive force and resistivity of the magnet, enhances the output power and energy efficiency of the permanent magnet motor, and improves the bending strength and magnetic properties of the magnet.
Smart Images

Figure CN119542022A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of permanent magnets, and in particular to a low eddy current loss permanent magnetic material. Background Art
[0002] Rare earth permanent magnet materials are a kind of metal functional materials that have developed rapidly in recent years. They are widely used in aerospace, transportation, electronic communications, etc. With the expansion of the application of rare earth permanent magnet materials, new and higher requirements are also put forward for the performance of materials. In particular, when rare earth permanent magnet materials work in a high-frequency alternating electric field environment, eddy currents are formed inside due to electromagnetic induction. The eddy currents cause the magnet itself to heat up and the magnetic properties to decrease. This phenomenon is called eddy current loss. In order to avoid eddy current loss and the working magnetic field is not required to be high, ferrite permanent magnet materials with lower magnetic properties but better insulation properties are generally used. However, this will lead to a relatively large volume of permanent magnet devices, which is not conducive to the miniaturization, lightweight and energy saving of devices. In the case of high magnetic field requirements, such as in the field of high-speed motors, rare earth permanent magnet materials with high magnetic properties must be used. Therefore, it is of great significance to develop sintered rare earth permanent magnet materials with low eddy current loss and high magnetic properties.
[0003] However, compared with ferrite materials, sintered Nd-Fe-B materials are not without disadvantages. The losses caused by eddy currents will also seriously affect the magnetic properties of sintered Nd-Fe-B materials. At the same time, Nd-Fe-B-based sintered magnets consume a large amount of heavy rare earth (HRE) elements Dy and Tb.
[0004] Compared with traditional induction motors and DC motors, permanent magnet synchronous motors have the advantages of strong torque capacity and high efficiency when using high magnetic co-energy sintered NdFeB magnets. However, when running at high frequencies, the eddy current loss generated by permanent magnets is very large, which will cause a high temperature rise in the permanent magnets, making them face the risk of irreversible demagnetization. Summary of the invention
[0005] The technical purpose of the present invention is to solve the problems in the background technology and provide a low eddy current loss permanent magnet material.
[0006] The above technical objectives of the present invention are achieved through the following technical solutions: A low eddy current loss permanent magnetic material, the preparation of which comprises the following steps: Step S1: Preparation of main phase raw materials: PrNd, Dy, Fe, B and M element magnet raw materials are prepared according to (Nd-Pr-Dy) x Fe y M z B bal Weigh and compound the ratio, where (x+y+z+bal)=100; Step S2: preparing the main phase raw material casting sheet: melting and pouring the raw material prepared in step S1 to obtain the main phase casting sheet; Step S3: preparing the synergistic grain boundary diffusion material casting sheet: melting and pouring the synergistic grain boundary diffusion material to obtain the synergistic grain boundary diffusion material casting sheet; Step S4: Preparation of composite coarse powder: Compound the castings in steps S2 and S3 according to a certain ratio, and send them into a hydrogen cracking furnace for hydrogen cracking to obtain composite coarse powder; Step S5: preparing fine powder: mixing the S4 composite coarse powder with a lubricant and an antioxidant, and then subjecting the mixture to air jet milling to obtain fine powder after collision grinding for a certain period of time; Step S6: preparing a green body: mixing the S5 fine powder with a binder and a solvent, sieving, and then forming and isostatically pressing to obtain a green body; Step S7: heat treatment of the magnet: sintering and secondary aging treatment are performed on the green body obtained in step S6 to obtain the final magnet.
[0007] Preferably, in step S1, the total amount of rare earth elements (Pr+Nd+Dy) is between 30-33 parts, Dy is between 0.5-2.0 parts, and the mass ratio of Pr:Nd is 20:80 or 25:75.
[0008] Preferably, in step S1, the mass fraction of Fe is 60-68 parts; the M element is one or more of copper Cu, manganese Mn, zirconium Zr, gallium Ga and silicon Si, and the mass fraction thereof is 0.5-1 part; and the remaining parts out of 100 parts are the boron element B component.
[0009] Preferably, in step S2, the magnetic powder is refined to a particle size below 3.0 μm.
[0010] The invention has the advantage that the magnetic powder is processed through fine machining to make its particle size less than three microns, which can significantly reduce the size of the magnetic powder, make the reaction more complete and concentrated, and be of great help to the subsequent steps.
[0011] Preferably, in step S3, the collaborative grain boundary diffusion treatment material is Tb x Al y Cu z , wherein x accounts for 60-80 parts, y accounts for 15-30 parts, z accounts for 5-10 parts, and the total mass fraction is 100 parts, and the mass percentage of the mixed magnetic powder obtained in step S2 is between 0.3% and 1%, and Tb x Al y Cu zThe particle size is controlled at 0.1-0.5 μm; the smelting casting process is as follows: after the raw materials are prepared, the vacuum system can be stopped when the vacuum degree in the furnace reaches a specified value, and then argon is filled into the furnace and the high-frequency induction current is turned on to start heating. After the alloy is completely melted, it is refined at 1300-1500°C for 3-5 minutes; then the casting system is started, the crucible is slowly poured, and the molten alloy liquid is poured into the tundish. Through the opening of the tundish, the slurry drips uniformly onto the high-speed rotating copper roller, the linear speed of the copper roller surface is controlled to obtain a faster cooling speed, and a quick-solidified casting sheet is obtained after cooling.
[0012] The invention has the advantages of utilizing the Tb-Al-Cu synergistic grain boundary diffusion process to simultaneously enhance the coercive force and resistivity of the Nd-Fe-B rotor magnet, thereby obtaining an optimized diffused magnet, and, due to the smaller particle size, the Tb-Al-Cu can be more evenly distributed around the main phase, and this structure not only promotes the formation of a highly anisotropic Tb-rich shell of the entire magnet main phase grain, but also improves the uniformity of the Tb-rich shell thickness, and accelerates the formation of high-resistivity intergranular base oxides. Due to the combination of enhanced magnetothermal stability and eddy current loss induction, the output power and energy efficiency of the permanent magnet motor can be improved.
[0013] Preferably, hydrogen is injected into the casting environment in step S4, and a certain amount of hydrogen absorbed by the casting will be removed after hydrogen decomposition is completed, and the remaining hydrogen is retained until dehydrogenation in the sintering stage in step S6.
[0014] The advantage of the present invention is that, unlike the conventional process, the present invention turns the dehydrogenation process to an interlaced process, thereby reducing the residual impurities inside it, which is beneficial to improving the magnetic properties of the magnet: in this hydrogen decay (HD) stage, only hydrogen is absorbed without dehydrogenation. Since hydrogen is a good reducing agent, the dehydrogenation stage is maintained until the sintering stage, and hydrogen can be completely combined with nitrogen and carbon in the magnetization, that is, hydrogen-containing sintering in the present invention. Therefore, in the hydrogen-containing sintering stage, nitrogen and carbon elements will be released together with hydrogen to reduce the residual impurities in the magnetic powder.
[0015] Preferably, the casting is ground in the air flow mill for 0.5-1.5h; an antioxidant and a lubricant are also added in step S5; the mass fractions of the lubricant and the antioxidant are 0.05-0.12 parts, of which 0.03-0.08 parts are antioxidants and 0.02-0.04 parts are lubricants; the rest are the magnetic powder after the above treatment, with a total mass fraction of 100 parts.
[0016] The invention has the advantage that the lubricant and the oxidant are added before the airflow mill, which not only prevents the magnetic powder from being oxidized and denatured, but also improves the grinding speed of the magnetic powder and reduces the defects generated in the collision process by adding the lubricant, improves the arrangement of the powder in the process of forming the magnetic field, and thus increases the maximum magnetic product energy (BH) of the magnet.max .
[0017] The advantage of adopting the present invention is that the fluidity of NdFeB permanent magnet powder particles is poor. Adding appropriate lubricant to the powder for spray grinding can reduce the friction between powder particles, prevent powder particles from agglomerating, and improve the fluidity of the powder. The powder fluidity of sintered NdFeB magnets is closely related to the orientation, remanence and magnetic energy product of the magnet. In the loose state, when the magnetic powder density is small, the main factor affecting the powder fluidity is the agglomeration of magnetic powder particles; when the magnetic powder is compacted and the density is high, the main factor affecting the fluidity of the magnetic powder is the friction between powder particles. The addition of lubricant has no obvious effect on overcoming the agglomeration of magnetic powder, but it has a significant effect on overcoming the powder friction of the block with a higher density and improving the orientation of the magnet, thereby significantly improving the remanence and magnetic energy product of the magnet.
[0018] Preferably, the green embryo forming process in step S6 is to press and form the green embryo in a 2.0-2.5T pulsed magnetic field, 180-200MPa isostatic pressure and a green embryo density of 50-60%, and the whole process is carried out in a nitrogen-protected glove box; the dehydrogenation sintering is carried out in a vacuum environment, and after the casting is saturated with hydrogen, the excess hydrogen is evacuated by a vacuum system, and the furnace body is heated to 950°C-1100°C for sintering for 5-10h; after the dehydrogenation sintering is completed, the heating system is turned off to cool the alloy to room temperature with argon gas; Preferably, an adhesive and a solvent are further added in step S6, wherein the adhesive is a volatile organic compound and the solvent is gasoline; the mass fractions of the adhesive and the solvent are 0.35-0.6 parts, of which the adhesive is 0.05-0.1 parts and the solvent is 0.3-0.5 parts; the rest is the magnetic powder after the above treatment, and the total mass fraction is 100 parts.
[0019] Preferably, the above procedure proceeds to the next step after the abrasive is passed through or the solvent in the abrasive is evaporated.
[0020] Preferably, in step S7, secondary aging treatment is performed, the first tempering heat treatment temperature is 850-950°C, the time is 3-5h, and the second tempering heat treatment temperature is 450°C-650°C, the time is 3-6h, to obtain the final permanent magnet material.
[0021] The advantage of the present invention is that the heat treatment method can better cope with the solution of the present invention, i.e., retaining hydrogen first and then removing hydrogen, and achieve a better sintering effect with the process. The permanent magnet thus obtained can achieve the technical effect of reducing eddy current loss by 20%, and the magnet obtained also has mechanical properties such as bending strength ≥ 300 MPa, Young's modulus: 150~200 GPa, and compressive strength ≥ 600 MPa; magnetic properties such as remanence Br ≥ 13.95 kG, coercive force Hcj ≥ 30 kOe, and maximum magnetic energy product (BH)max :46.98-51MGOe.
[0022] In summary, the present invention has the following beneficial effects: 1. Through Tb x Al y Cu z The introduction of cooperative grain boundary diffusion materials and the method of simultaneously enhancing the coercivity and resistivity of Nd-Fe-B rotor magnets by the Tb-Al-Cu cooperative grain boundary diffusion process can obtain optimized diffused magnets, while improving the output power and energy efficiency of the motor; 2. By absorbing hydrogen first and then dehydrogenating it during the sintering stage, combined with the addition of volatile adhesives, it is possible to leave no impurities. This process can not only improve the anti-eddy current loss performance of the magnet, but also enhance the coercive force; 3. In the process, for each step that requires fine powder to purify the magnet, the particle size is kept below 3.0μm, which can control the average particle size and distribution of the magnetic powder and improve the inherent coercive force of the sintered magnet. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] FIG1 is a flow chart of a process for preparing a low eddy current loss permanent magnet material. DETAILED DESCRIPTION
[0024] The following specific embodiments are merely explanations of the present invention and are not intended to limit the present invention.
[0025] It should be noted that, in the present invention, M metal uniformly adopts Cu element, but in practice it may include but is not limited to this metal element (a combination of multiple metal elements in the specification); in the embodiment of the present invention, the default total number of mass parts is 100 parts, which will not be elaborated in detail below.
[0026] Example 1
[0027] Step S1: Preparation of main phase raw materials: PrNd, Dy, Fe, B and M element magnet raw materials are prepared according to (Nd-Pr-Dy) x Fe y M z B bal The proportions are weighed and compounded, wherein the total amount of (Pr+Nd+Dy) is 33 parts, the mass ratio of Pr to Nd is 20:80, the mass portion of Dy is 2 parts, and the rest are Pr and Nd in proportion; the rest are 60 parts of Fe powder, 1 part of Cu powder, and the remaining parts in 100 parts are the boron element B component.
[0028] Step S2: preparing the main phase raw material casting sheet: the raw material prepared in step S1 is smelted and cast to obtain the main phase casting sheet, and the casting sheet is further refined to a uniform powder with a particle size of ≤3.0 μm; Step S3 Preparation of Synergistic Grain Boundary Diffusion Material Casting Sheet: Melting and pouring the Synergistic Grain Boundary Diffusion Material to obtain the Synergistic Grain Boundary Diffusion Material Casting Sheet; the Synergistic Grain Boundary Diffusion Processed Material is Tb x Al y Cu z , Tb x Al y Cu z The particle size is controlled at 0.1-0.5 μm, of which x accounts for 60 parts, y accounts for 30 parts, and z accounts for 10 parts.
[0029] Step S4 preparation of composite coarse powder: the flakes obtained in step S3 are mixed with the fine powder obtained in step S2 at a mass percentage of 0.3% for compounding, and the vacuum system can be stopped when the vacuum degree in the furnace reaches the specified value, and then argon is filled into the furnace and the high-frequency induction current is turned on to start heating. After the alloy is completely melted, it is refined at 1300°C for 5 minutes; then the casting system is started, the crucible is slowly poured, and the molten alloy liquid is poured into the tundish. Through the opening of the tundish, the slurry drips uniformly onto the high-speed rotating copper roller, and the linear speed of the copper roller surface is controlled to obtain a faster cooling rate. After cooling, the flake coarse powder is obtained, and hydrogen is injected during the casting process. The hydrogen absorbed by the flakes will remove a certain amount of hydrogen after the hydrogen decomposition is completed, and the remaining hydrogen is retained until the sintering stage in step S6 for dehydrogenation.
[0030] Step S5: Preparation of fine powder: Grind the S4 cast flake powder in a jet mill for 0.5 h; and add an antioxidant and a lubricant; the mass fraction of the lubricant and antioxidant is 0.05 parts, of which 0.03 parts are antioxidants and 0.02 parts are lubricants; the rest is the magnetic powder after the above treatment, and the total mass fraction is 100 parts; Step S6 green billet preparation: S5 fine powder is mixed with a binder and a solvent, and then sieved and molded and isostatically pressed, wherein the binder is a volatile organic matter and the solvent is acetone; the mass fraction of the binder and the solvent is 0.35 parts, of which the binder is 0.05 parts and the solvent is 0.3 parts; the rest is the magnetic powder after the above treatment, and the total mass fraction is 100 parts; the molding process is to press and mold under a 2.0T pulse magnetic field, 180MPa isostatic pressure and a green billet density of 50%, and the whole process is carried out in a nitrogen-protected glove box; dehydrogenation sintering is carried out in a vacuum environment, and after the casting is saturated with hydrogen, the excess hydrogen is evacuated by a vacuum system, and the furnace body is heated to 950°C and sintered for 10 hours; after the dehydrogenation sintering is completed, the heating system is turned off and the alloy is argon-cooled to room temperature to obtain a green billet.
[0031] Step S7: heat treatment of magnet: the green body obtained in step S6 is sintered and subjected to secondary aging treatment. The first stage tempering heat treatment temperature is 850°C for 5 hours, and the second stage tempering heat treatment temperature is 650°C for 3 hours to obtain the final permanent magnet material.
[0032] Example 2
[0033] Step S1: Preparation of main phase raw materials: PrNd, Dy, Fe, B and M element magnet raw materials are prepared according to (Nd-Pr-Dy) x Fe y M z B bal The proportions are weighed and compounded, wherein the total amount of (Pr+Nd+Dy) is 30 parts, the mass ratio of Pr to Nd is 25:75, the mass portion of Dy is 0.5 parts, and the rest are Pr and Nd in proportion; the rest are 68 parts of Fe powder, 0.5 parts of Cu powder, and the remaining parts out of 100 parts are the boron element B component.
[0034] Step S2: preparing the main phase raw material casting sheet: the raw material prepared in step S1 is smelted and cast to obtain the main phase casting sheet, and the casting sheet is further refined to a uniform powder with a particle size of ≤3.0 μm; Step S3 Preparation of Synergistic Grain Boundary Diffusion Material Casting Sheet: Melting and pouring the Synergistic Grain Boundary Diffusion Material to obtain the Synergistic Grain Boundary Diffusion Material Casting Sheet; the Synergistic Grain Boundary Diffusion Processed Material is Tb x Al y Cu z , Tb x Al y Cu z The particle size is controlled at 0.1-0.5 μm, of which x accounts for 60 parts, y accounts for 30 parts, and z accounts for 10 parts.
[0035] Step S4 preparation of composite coarse powder: the flakes obtained in step S3 are mixed with the fine powder obtained in step S2 at a mass percentage of 0.3% for compounding, and the vacuum system can be stopped when the vacuum degree in the furnace reaches the specified value, and then argon is filled into the furnace and the high-frequency induction current is turned on to start heating. After the alloy is completely melted, it is refined at 1300°C for 5 minutes; then the casting system is started, the crucible is slowly poured, and the molten alloy liquid is poured into the tundish. Through the opening of the tundish, the slurry drips uniformly onto the high-speed rotating copper roller, the linear speed of the copper roller surface is controlled to obtain a faster cooling rate, and the flake coarse powder is obtained after cooling. Hydrogen is injected during the casting process. The hydrogen absorbed by the flakes will remove a certain amount of hydrogen after the hydrogen decomposition is completed, and the remaining hydrogen is retained until the sintering stage in step S6 for dehydrogenation.
[0036] Step S5: Preparation of fine powder: Grind the S4 cast flake powder in a jet mill for 0.5 h; and add an antioxidant and a lubricant; the mass fraction of the lubricant and antioxidant is 0.05 parts, of which 0.03 parts are antioxidants and 0.02 parts are lubricants; the rest is the magnetic powder after the above treatment, and the total mass fraction is 100 parts; Step S6 green billet preparation: S5 fine powder is mixed with a binder and a solvent, and then sieved and molded and isostatically pressed, wherein the binder is a volatile organic matter and the solvent is acetone; the mass fraction of the binder and the solvent is 0.35 parts, of which the binder is 0.05 parts and the solvent is 0.3 parts; the rest is the magnetic powder after the above treatment, and the total mass fraction is 100 parts; the molding process is to press and mold under a 2.0T pulse magnetic field, 180MPa isostatic pressure and a green billet density of 50%, and the whole process is carried out in a nitrogen-protected glove box; dehydrogenation sintering is carried out in a vacuum environment, and after the casting is saturated with hydrogen, the excess hydrogen is evacuated by a vacuum system, and the furnace body is heated to 950°C and sintered for 10 hours; after the dehydrogenation sintering is completed, the heating system is turned off and the alloy is argon-cooled to room temperature to obtain a green billet.
[0037] Step S7: heat treatment of magnet: the green body obtained in step S6 is sintered and subjected to secondary aging treatment. The first stage tempering heat treatment temperature is 850°C for 5 hours, and the second stage tempering heat treatment temperature is 650°C for 3 hours to obtain the final permanent magnet material.
[0038] Example 3
[0039] Step S1: Preparation of main phase raw materials: PrNd, Dy, Fe, B and M element magnet raw materials are prepared according to (Nd-Pr-Dy) x Fe y M z B bal The proportions are weighed and compounded, wherein the total amount of (Pr+Nd+Dy) is 30.2 parts, the mass ratio of Pr to Nd is 25:75, the mass portion of Dy is 1.2 parts, and the rest are Pr and Nd in proportion; the rest are 67.5 parts of Fe powder, 0.8 parts of Cu powder, and the remaining parts out of 100 parts are the boron element B component.
[0040] Step S2: preparing the main phase raw material casting sheet: the raw material prepared in step S1 is smelted and cast to obtain the main phase casting sheet, and the casting sheet is further refined to a uniform powder with a particle size of ≤3.0 μm; Step S3 Preparation of Synergistic Grain Boundary Diffusion Material Casting Sheet: Melting and pouring the Synergistic Grain Boundary Diffusion Material to obtain the Synergistic Grain Boundary Diffusion Material Casting Sheet; the Synergistic Grain Boundary Diffusion Processed Material is Tb x Al y Cu z , Tb x Al y Cu z The particle size is controlled at 0.1-0.5 μm, of which x accounts for 80 parts, y accounts for 15 parts, z accounts for 5 parts, and the total mass parts are 100 parts.
[0041] Step S4 preparation of composite coarse powder: the flakes obtained in step S3 are mixed with the fine powder obtained in step S2 at a mass percentage of 0.8% for compounding, and the vacuum system can be stopped when the vacuum degree in the furnace reaches the specified value, and then argon is filled into the furnace and the high-frequency induction current is turned on to start heating. After the alloy is completely melted, it is refined at 1400°C for 5 minutes; then the casting system is started, the crucible is slowly poured, and the molten alloy liquid is poured into the tundish. Through the opening of the tundish, the slurry drips uniformly onto the high-speed rotating copper roller, and the linear speed of the copper roller surface is controlled to obtain a faster cooling rate. After cooling, the flake coarse powder is obtained, and hydrogen is injected during the casting process. The hydrogen absorbed by the flakes will remove a certain amount of hydrogen after the hydrogen decomposition is completed, and the remaining hydrogen is retained until the sintering stage in step S6 for dehydrogenation.
[0042] Step S5: Preparation of fine powder: Grind the S4 cast flake powder in a jet mill for 0.75 h; and add an antioxidant and a lubricant; the mass fraction of the lubricant and antioxidant is 0.08 parts, of which 0.05 parts are antioxidants and 0.03 parts are lubricants; the rest is the magnetic powder after the above treatment, and the total mass fraction is 100 parts; Step S6 green billet preparation: S5 fine powder is mixed with a binder and a solvent, and then sieved and molded and isostatically pressed, wherein the binder is a volatile organic matter and the solvent is acetone; the mass fractions of the binder and the solvent are 0.6 parts, of which the binder is 0.1 parts and the solvent is 0.5 parts; the rest are magnetic powders after the above treatment, and the total mass fractions are 100 parts; the molding process is to press and mold under a 2.5T pulse magnetic field, 200MPa isostatic pressure and a green billet density of 60%, and the whole process is carried out in a nitrogen-protected glove box; dehydrogenation sintering is carried out in a vacuum environment, and after the casting is saturated with hydrogen, the excess hydrogen is evacuated by a vacuum system, and the furnace body is heated to 1100°C and sintered for 5 hours; after the dehydrogenation sintering is completed, the heating system is turned off and the alloy is cooled to room temperature with argon gas to obtain a green billet.
[0043] Step S7: heat treatment of magnet: the green body obtained in step S6 is sintered and subjected to secondary aging treatment. The first stage tempering heat treatment temperature is 950°C for 5 hours, and the second stage tempering heat treatment temperature is 650°C for 3 hours to obtain the final permanent magnet material.
[0044] Example 4
[0045] Step S1: Preparation of main phase raw materials: PrNd, Dy, Fe, B and M element magnet raw materials are prepared according to (Nd-Pr-Dy) x Fe y M z B balThe proportions are weighed and compounded, wherein the total amount of (Pr+Nd+Dy) is 30.2 parts, the mass ratio of Pr to Nd is 25:75, the mass portion of Dy is 1.2 parts, and the rest are Pr and Nd in proportion; the rest are 67.5 parts of Fe powder, 0.8 parts of Cu powder, and the remaining parts out of 100 parts are the boron element B component.
[0046] Step S2: preparing the main phase raw material casting sheet: the raw material prepared in step S1 is smelted and cast to obtain the main phase casting sheet, and the casting sheet is further refined to a uniform powder with a particle size of ≤3.0 μm; Step S3 Preparation of Synergistic Grain Boundary Diffusion Material Casting Sheet: Melting and pouring the Synergistic Grain Boundary Diffusion Material to obtain the Synergistic Grain Boundary Diffusion Material Casting Sheet; the Synergistic Grain Boundary Diffusion Processed Material is Tb x Al y Cu z , Tb x Al y Cu z The particle size is controlled at 0.1-0.5 μm, of which x accounts for 70 parts, y accounts for 20 parts, and z accounts for 10 parts.
[0047] Step S4 preparation of composite coarse powder: the flakes obtained in step S3 are mixed with the fine powder obtained in step S2 at a mass percentage of 0.8% for compounding, and the vacuum system can be stopped when the vacuum degree in the furnace reaches the specified value, and then argon is filled into the furnace and the high-frequency induction current is turned on to start heating. After the alloy is completely melted, it is refined at 1400°C for 5 minutes; then the casting system is started, the crucible is slowly poured, and the molten alloy liquid is poured into the tundish. Through the opening of the tundish, the slurry drips uniformly onto the high-speed rotating copper roller, and the linear speed of the copper roller surface is controlled to obtain a faster cooling rate. After cooling, the flake coarse powder is obtained, and hydrogen is injected during the casting process. The hydrogen absorbed by the flakes will remove a certain amount of hydrogen after the hydrogen decomposition is completed, and the remaining hydrogen is retained until the sintering stage in step S6 for dehydrogenation.
[0048] Step S5: Preparation of fine powder: Grind the S4 cast flake powder in a jet mill for 0.75 h; and add an antioxidant and a lubricant; the mass fraction of the lubricant and antioxidant is 0.08 parts, of which 0.05 parts are antioxidants and 0.03 parts are lubricants; the rest is the magnetic powder after the above treatment, and the total mass fraction is 100 parts; Step S6 green billet preparation: S5 fine powder is mixed with a binder and a solvent, and then sieved and molded and isostatically pressed, wherein the binder is a volatile organic matter and the solvent is acetone; the mass fractions of the binder and the solvent are 0.6 parts, of which the binder is 0.1 parts and the solvent is 0.5 parts; the rest are magnetic powders after the above treatment, and the total mass fractions are 100 parts; the molding process is to press and mold under a 2.5T pulse magnetic field, 200MPa isostatic pressure and a green billet density of 60%, and the whole process is carried out in a nitrogen-protected glove box; dehydrogenation sintering is carried out in a vacuum environment, and after the casting is saturated with hydrogen, the excess hydrogen is evacuated by a vacuum system, and the furnace body is heated to 1100°C and sintered for 5 hours; after the dehydrogenation sintering is completed, the heating system is turned off and the alloy is cooled to room temperature with argon gas to obtain a green billet.
[0049] Step S7: heat treatment of magnet: the green body obtained in step S6 is sintered and subjected to secondary aging treatment. The first stage tempering heat treatment temperature is 950°C for 5 hours, and the second stage tempering heat treatment temperature is 650°C for 3 hours to obtain the final permanent magnet material.
[0050] Example 5
[0051] Step S1: Preparation of main phase raw materials: PrNd, Dy, Fe, B and M element magnet raw materials are prepared according to (Nd-Pr-Dy) x Fe y M z B bal The proportions are weighed and compounded, wherein the total amount of (Pr+Nd+Dy) is 30.2 parts, the mass ratio of Pr to Nd is 25:75, the mass portion of Dy is 1.2 parts, and the rest are Pr and Nd in proportion; the rest are 67.5 parts of Fe powder, 0.8 parts of Cu powder, and the remaining parts out of 100 parts are the boron element B component.
[0052] Step S2: preparing the main phase raw material casting sheet: the raw material prepared in step S1 is smelted and cast to obtain the main phase casting sheet, and the casting sheet is further refined to a uniform powder with a particle size of ≤3.0 μm; Step S3 Preparation of Synergistic Grain Boundary Diffusion Material Casting Sheet: Melting and pouring the Synergistic Grain Boundary Diffusion Material to obtain the Synergistic Grain Boundary Diffusion Material Casting Sheet; the Synergistic Grain Boundary Diffusion Processed Material is Tb x Al y Cu z , Tb x Al y Cu z The particle size is controlled at 0.1-0.5 μm, of which x accounts for 70 parts, y accounts for 20 parts, and z accounts for 10 parts.
[0053] Step S4 preparation of composite coarse powder: the flakes obtained in step S3 are mixed with the fine powder obtained in step S2 at a mass percentage of 0.8% for compounding, and the vacuum system can be stopped when the vacuum degree in the furnace reaches the specified value, and then argon is filled into the furnace and the high-frequency induction current is turned on to start heating. After the alloy is completely melted, it is refined at 1400°C for 5 minutes; then the casting system is started, the crucible is slowly poured, and the molten alloy liquid is poured into the tundish. Through the opening of the tundish, the slurry drips uniformly onto the high-speed rotating copper roller, and the linear speed of the copper roller surface is controlled to obtain a faster cooling rate. After cooling, the flake coarse powder is obtained, and hydrogen is injected during the casting process. The hydrogen absorbed by the flakes will remove a certain amount of hydrogen after the hydrogen decomposition is completed, and the remaining hydrogen is retained until the sintering stage in step S6 for dehydrogenation.
[0054] Step S5: Preparation of fine powder: Grind the S4 cast flake powder in a jet mill for 1 hour; and add an antioxidant and a lubricant; the mass fraction of the lubricant and antioxidant is 0.08 parts, of which 0.06 parts are antioxidants and 0.028 parts are lubricants; the rest is the magnetic powder after the above treatment, and the total mass fraction is 100 parts; Step S6 green billet preparation: S5 fine powder is mixed with a binder and a solvent, and then sieved and molded and isostatically pressed, wherein the binder is a volatile organic matter and the solvent is acetone; the mass fractions of the binder and the solvent are 0.6 parts, of which the binder is 0.1 parts and the solvent is 0.5 parts; the rest are magnetic powders after the above treatment, and the total mass fractions are 100 parts; the molding process is to press and mold under a 2.5T pulse magnetic field, 200MPa isostatic pressure and a green billet density of 60%, and the whole process is carried out in a nitrogen-protected glove box; dehydrogenation sintering is carried out in a vacuum environment, and after the casting is saturated with hydrogen, the excess hydrogen is evacuated by a vacuum system, and the furnace body is heated to 1100°C and sintered for 5 hours; after the dehydrogenation sintering is completed, the heating system is turned off and the alloy is cooled to room temperature with argon gas to obtain a green billet.
[0055] Step S7: heat treatment of magnet: the green body obtained in step S6 is sintered and subjected to secondary aging treatment. The first stage tempering heat treatment temperature is 950°C for 5 hours, and the second stage tempering heat treatment temperature is 650°C for 3 hours to obtain the final permanent magnet material.
[0056] Example 6
[0057] Step S1: Preparation of main phase raw materials: PrNd, Dy, Fe, B and M element magnet raw materials are prepared according to (Nd-Pr-Dy) x Fe y M z B balThe proportions are weighed and compounded, wherein the total amount of (Pr+Nd+Dy) is 30.2 parts, the mass ratio of Pr to Nd is 25:75, the mass portion of Dy is 1.2 parts, and the rest are Pr and Nd in proportion; the rest are 67.5 parts of Fe powder, 0.8 parts of Cu powder, and the remaining parts out of 100 parts are the boron element B component.
[0058] Step S2: preparing the main phase raw material casting sheet: the raw material prepared in step S1 is smelted and cast to obtain the main phase casting sheet, and the casting sheet is further refined to a uniform powder with a particle size of ≤3.0 μm; Step S3 Preparation of Synergistic Grain Boundary Diffusion Material Casting Sheet: Melting and pouring the Synergistic Grain Boundary Diffusion Material to obtain the Synergistic Grain Boundary Diffusion Material Casting Sheet; the Synergistic Grain Boundary Diffusion Processed Material is Tb x Al y Cu z , Tb x Al y Cu z The particle size is controlled at 0.1-0.5 μm, of which x accounts for 70 parts, y accounts for 20 parts, and z accounts for 10 parts.
[0059] Step S4 preparation of composite coarse powder: the flakes obtained in step S3 are mixed with the fine powder obtained in step S2 at a mass percentage of 0.8% for compounding, and the vacuum system can be stopped when the vacuum degree in the furnace reaches the specified value, and then argon is filled into the furnace and the high-frequency induction current is turned on to start heating. After the alloy is completely melted, it is refined at 1400°C for 5 minutes; then the casting system is started, the crucible is slowly poured, and the molten alloy liquid is poured into the tundish. Through the opening of the tundish, the slurry drips uniformly onto the high-speed rotating copper roller, and the linear speed of the copper roller surface is controlled to obtain a faster cooling rate. After cooling, the flake coarse powder is obtained, and hydrogen is injected during the casting process. The hydrogen absorbed by the flakes will remove a certain amount of hydrogen after the hydrogen decomposition is completed, and the remaining hydrogen is retained until the sintering stage in step S6 for dehydrogenation.
[0060] Step S5: Preparation of fine powder: Grind the S4 cast flake powder in a jet mill for 0.8 h; and add an antioxidant and a lubricant; the mass fraction of the lubricant and antioxidant is 0.1 parts, of which the antioxidant is 0.07 parts and the lubricant is 0.035 parts; the rest is the magnetic powder after the above treatment, and the total mass fraction is 100 parts; Step S6 green billet preparation: S5 fine powder is mixed with a binder and a solvent, and then sieved and molded and isostatically pressed, wherein the binder is a volatile organic matter and the solvent is acetone; the mass fractions of the binder and the solvent are 0.6 parts, of which the binder is 0.1 parts and the solvent is 0.5 parts; the rest are magnetic powders after the above treatment, and the total mass fractions are 100 parts; the molding process is to press and mold under a 2.5T pulse magnetic field, 200MPa isostatic pressure and a green billet density of 60%, and the whole process is carried out in a nitrogen-protected glove box; dehydrogenation sintering is carried out in a vacuum environment, and after the casting is saturated with hydrogen, the excess hydrogen is evacuated by a vacuum system, and the furnace body is heated to 1100°C and sintered for 5 hours; after the dehydrogenation sintering is completed, the heating system is turned off and the alloy is cooled to room temperature with argon gas to obtain a green billet.
[0061] Step S7: heat treatment of magnet: the green body obtained in step S6 is sintered and subjected to secondary aging treatment. The first stage tempering heat treatment temperature is 950°C for 5 hours, and the second stage tempering heat treatment temperature is 650°C for 3 hours to obtain the final permanent magnet material.
[0062] Example 7
[0063] Step S1: Preparation of main phase raw materials: PrNd, Dy, Fe, B and M element magnet raw materials are prepared according to (Nd-Pr-Dy) x Fe y M z B bal The proportions are weighed and compounded, wherein the total amount of (Pr+Nd+Dy) is 30.2 parts, the mass ratio of Pr to Nd is 25:75, the mass portion of Dy is 1.2 parts, and the rest are Pr and Nd in proportion; the rest are 67.5 parts of Fe powder, 0.8 parts of Cu powder, and the remaining parts out of 100 parts are the boron element B component.
[0064] Step S2: preparing the main phase raw material casting sheet: the raw material prepared in step S1 is smelted and cast to obtain the main phase casting sheet, and the casting sheet is further refined to a uniform powder with a particle size of ≤3.0 μm; Step S3 Preparation of Synergistic Grain Boundary Diffusion Material Casting Sheet: Melting and pouring the Synergistic Grain Boundary Diffusion Material to obtain the Synergistic Grain Boundary Diffusion Material Casting Sheet; the Synergistic Grain Boundary Diffusion Processed Material is Tb x Al y Cu z , Tb x Al y Cu z The particle size is controlled at 0.1-0.5 μm, of which x accounts for 70 parts, y accounts for 20 parts, and z accounts for 10 parts.
[0065] Step S4 preparation of composite coarse powder: the flakes obtained in step S3 are mixed with the fine powder obtained in step S2 at a mass percentage of 0.8% for compounding, and the vacuum system can be stopped when the vacuum degree in the furnace reaches the specified value, and then argon is filled into the furnace and the high-frequency induction current is turned on to start heating. After the alloy is completely melted, it is refined at 1400°C for 5 minutes; then the casting system is started, the crucible is slowly poured, and the molten alloy liquid is poured into the tundish. Through the opening of the tundish, the slurry drips uniformly onto the high-speed rotating copper roller, and the linear speed of the copper roller surface is controlled to obtain a faster cooling rate. After cooling, the flake coarse powder is obtained, and hydrogen is injected during the casting process. The hydrogen absorbed by the flakes will remove a certain amount of hydrogen after the hydrogen decomposition is completed, and the remaining hydrogen is retained until the sintering stage in step S6 for dehydrogenation.
[0066] Step S5: Preparation of fine powder: Grind the S4 cast flake powder in a jet mill for 0.8 h; and add an antioxidant and a lubricant; the mass fraction of the lubricant and antioxidant is 0.1 parts, of which the antioxidant is 0.07 parts and the lubricant is 0.035 parts; the rest is the magnetic powder after the above treatment, and the total mass fraction is 100 parts; Step S6 green billet preparation: S5 fine powder is mixed with a binder and a solvent, and then sieved and molded and isostatically pressed, wherein the binder is a volatile organic matter and the solvent is acetone; the mass fractions of the binder and the solvent are 0.48 parts, of which the binder is 0.08 parts and the solvent is 0.39 parts; the rest are magnetic powders after the above treatment, and the total mass fractions are 100 parts; the molding process is to press and mold under a 2.4T pulse magnetic field, 190MPa isostatic pressure and a green billet density of 60%, and the whole process is carried out in a nitrogen-protected glove box; dehydrogenation sintering is carried out in a vacuum environment, and after the casting is saturated with hydrogen, the excess hydrogen is evacuated by a vacuum system, and the furnace body is heated to 1000°C and sintered for 8 hours; after the dehydrogenation sintering is completed, the heating system is turned off and the alloy is cooled to room temperature with argon gas to obtain a green billet.
[0067] Step S7: heat treatment of magnet: the green body obtained in step S6 is sintered and subjected to secondary aging treatment. The first stage tempering heat treatment temperature is 950°C for 4 hours, and the second stage tempering heat treatment temperature is 550°C for 5 hours to obtain the final permanent magnet material.
[0068] Comparative Example 1
[0069] Different from the above-mentioned Example 7, this comparative example does not add the process of hydrogen absorption, and the hydrogen destruction process is directly completed during the casting process.
[0070] Step S1: Preparation of main phase raw materials: PrNd, Dy, Fe, B and M element magnet raw materials are prepared according to (Nd-Pr-Dy) x Fe y M z B balThe proportions are weighed and compounded, wherein the total amount of (Pr+Nd+Dy) is 30.2 parts, the mass ratio of Pr to Nd is 25:75, the mass portion of Dy is 1.2 parts, and the rest are Pr and Nd in proportion; the rest are 67.5 parts of Fe powder, 0.8 parts of Cu powder, and the remaining parts out of 100 parts are the boron element B component.
[0071] Step S2: preparing the main phase raw material casting sheet: the raw material prepared in step S1 is smelted and cast to obtain the main phase casting sheet, and the casting sheet is further refined to a uniform powder with a particle size of ≤3.0 μm; Step S3 Preparation of Synergistic Grain Boundary Diffusion Material Casting Sheet: Melting and pouring the Synergistic Grain Boundary Diffusion Material to obtain the Synergistic Grain Boundary Diffusion Material Casting Sheet; the Synergistic Grain Boundary Diffusion Processed Material is Tb x Al y Cu z , of which x accounts for 70, y accounts for 20, and z accounts for 10.
[0072] Step S4 preparation of composite coarse powder: the flakes obtained in step S3 are added to the fine powder obtained in step S2 at a mass percentage of 0.8% for compounding, and the vacuum system can be stopped when the vacuum degree in the furnace reaches the specified value. Then, argon is filled into the furnace and the high-frequency induction current is turned on to start heating. After the alloy is completely melted, it is refined at 1400°C for 5 minutes; then the casting system is started, the crucible is slowly poured, and the molten alloy liquid is poured into the tundish. Through the opening of the tundish, the slurry drips uniformly onto the high-speed rotating copper roller, the linear speed of the copper roller surface is controlled to obtain a faster cooling rate, and the flake coarse powder is obtained after cooling, and hydrogen cracking is also completed during the casting process.
[0073] Step S5: Preparation of fine powder: Grind the S4 cast flake powder in a jet mill for 0.8 h; and add an antioxidant; the mass fraction of lubricant and antioxidant is 0.1 parts, of which 0.07 parts are antioxidant and 0.035 parts are lubricant; the rest is the magnetic powder after the above treatment, and the total mass fraction is 100 parts; Step S6 green body preparation: S5 fine powder is mixed with a binder and a solvent, sieved, and then molded and isostatically pressed, wherein the binder is a thermosetting binder and the solvent is acetone; the mass fractions of the binder and the solvent are 0.48 parts, of which the binder is 0.08 parts and the solvent is 0.39 parts; the rest are magnetic powders after the above treatment, with a total mass fraction of 100 parts; the molding process is compression molding under a 2.4T pulsed magnetic field, 190MPa isostatic pressure and a green body density of 60%, and the entire process is carried out in a nitrogen-protected glove box.
[0074] Step S7: heat treatment of magnet: the green body obtained in step S6 is sintered and subjected to secondary aging treatment. The first stage tempering heat treatment temperature is 950°C for 4 hours, and the second stage tempering heat treatment temperature is 550°C for 5 hours to obtain the final permanent magnet material.
[0075] Comparative Example 2
[0076] The difference from the above comparative example is that in this comparative example, the particle refining process is further cancelled, and no further refining treatment is performed after the crushing process.
[0077] Step S1: Preparation of main phase raw materials: PrNd, Dy, Fe, B and M element magnet raw materials are prepared according to (Nd-Pr-Dy) x Fe y M z B bal The proportions are weighed and compounded, wherein the total amount of (Pr+Nd+Dy) is 30.2 parts, the mass ratio of Pr to Nd is 25:75, the mass portion of Dy is 1.2 parts, and the rest are Pr and Nd in proportion; the rest are 67.5 parts of Fe powder, 0.8 parts of Cu powder, and the remaining parts out of 100 parts are the boron element B component.
[0078] Step S2: preparing the main phase raw material casting sheet: melting and pouring the raw material prepared in step S1 to obtain the main phase casting sheet; Step S3 Preparation of Synergistic Grain Boundary Diffusion Material Casting Sheet: Melting and pouring the Synergistic Grain Boundary Diffusion Material to obtain the Synergistic Grain Boundary Diffusion Material Casting Sheet; the Synergistic Grain Boundary Diffusion Processed Material is Tb x Al y Cu z , of which x accounts for 70, y accounts for 20, and z accounts for 10.
[0079] Step S4 preparation of composite coarse powder: the flakes obtained in step S3 are added to the fine powder obtained in step S2 at a mass percentage of 0.8% for compounding, and the vacuum system can be stopped when the vacuum degree in the furnace reaches the specified value. Then, argon is filled into the furnace and the high-frequency induction current is turned on to start heating. After the alloy is completely melted, it is refined at 1400°C for 5 minutes; then the casting system is started, the crucible is slowly poured, and the molten alloy liquid is poured into the tundish. Through the opening of the tundish, the slurry drips uniformly onto the high-speed rotating copper roller, the linear speed of the copper roller surface is controlled to obtain a faster cooling rate, and the flake coarse powder is obtained after cooling, and hydrogen cracking is also completed during the casting process.
[0080] Step S5: Preparation of fine powder: Grind the S4 cast flake powder in a jet mill for 0.8 h; and add an antioxidant; the mass fraction of lubricant and antioxidant is 0.1 parts, of which 0.07 parts are antioxidant and 0.035 parts are lubricant; the rest is the magnetic powder after the above treatment, and the total mass fraction is 100 parts; Step S6 green body preparation: S5 fine powder is mixed with a binder and a solvent, sieved, and then molded and isostatically pressed, wherein the binder is a thermosetting binder and the solvent is acetone; the mass fractions of the binder and the solvent are 0.48 parts, of which the binder is 0.08 parts and the solvent is 0.39 parts; the rest are magnetic powders after the above treatment, with a total mass fraction of 100 parts; the molding process is compression molding under a 2.4T pulsed magnetic field, 190MPa isostatic pressure and a green body density of 60%, and the entire process is carried out in a nitrogen-protected glove box.
[0081] Step S7: heat treatment of magnet: the green body obtained in step S6 is sintered and subjected to secondary aging treatment. The first stage tempering heat treatment temperature is 950°C for 4 hours, and the second stage tempering heat treatment temperature is 550°C for 5 hours to obtain the final permanent magnet material.
[0082] Comparative Example 3
[0083] The difference from the above comparative example is that the present comparative example further eliminates the grain boundary diffusion process, adds 0.8 parts of rare earth elements to the raw magnetic powder, and finally produces a permanent magnet.
[0084] The magnetic properties and eddy current loss reduction rates of the finished magnets obtained in the above-mentioned Examples 1-7 and Comparative Examples 1-3 were evaluated and tested.
[0085] The magnetic properties tested include remanence (kG), coercive force (kOe) and maximum magnetic product energy (MGoe).
[0086] The magnetic property testing method and determination refer to GBT 3217-2013 Magnetic test method for permanent magnetic (hard magnetic) materials; The eddy current power loss in the magnetic material is given by:
[0087] Where, Ke- eddy current coefficient; Bm-maximum value of magnetic flux density, wb / m; t-thickness of the lamination; f-reversal frequency of magnetic field, Hz; V-volume of magnetic material, m 3 .
[0088] Eddy current loss reduction percentage = (Pe2-Pe1) / Pe1 Wherein, Pe1 is normal eddy current loss, and Pe2 is eddy current loss obtained in the embodiment of the present invention.
[0089] The results are as follows: Table 1 Magnetic properties and eddy current loss reduction rate of permanent magnetic materials
[0090] It can be seen from the results in the above table that the magnet prepared under the conditions of Example 7 has the best magnetic properties and ability to resist eddy current losses.
[0091] Compared with Comparative Example 1, Comparative Example 1 does not adopt the special hydrogen treatment process in the scheme of the present invention, and directly removes all hydrogen in the previous hydrogen cracking process, which may not completely remove impurities in the magnet, so its magnetic performance and anti-eddy current performance are lower than those in the scheme of the present invention.
[0092] Compared with Comparative Example 2, Comparative Example 2 further eliminates the particle refinement process. Eliminating the refinement process makes the average particle size and distribution of the magnetic powder uneven, so the magnetic properties and anti-eddy current performance of the magnet finally obtained are poor.
[0093] Compared with Comparative Example 3, Comparative Example 3 discards the cooperative grain boundary diffusion material and directly places the rare earth element in the raw material composition. The magnet obtained in this way has a certain anti-eddy current loss function, but its effect is very poor compared with the product of the present invention. Therefore, the combined processes of the present invention are indispensable.
Claims
1. A low eddy current loss permanent magnetic material, characterized in that: Its preparation comprises the following steps: Step S1: Preparation of main phase raw materials: PrNd, Dy, Fe, B and M element magnet raw materials are prepared according to (Nd-Pr-Dy) x Fe y M z B bal Weigh and compound the ratio, where (x+y+z+bal)=100; Step S2: preparing the main phase raw material casting sheet: melting and pouring the raw material prepared in step S1 to obtain the main phase casting sheet; Step S3: preparing the synergistic grain boundary diffusion material casting sheet: melting and pouring the synergistic grain boundary diffusion material to obtain the synergistic grain boundary diffusion material casting sheet; Step S4: Preparation of composite coarse powder: Compound the castings in steps S2 and S3 according to a certain ratio, and send them into a hydrogen cracking furnace for hydrogen cracking to obtain composite coarse powder; Step S5: preparing fine powder: mixing the S4 composite coarse powder with a lubricant and an antioxidant, and then subjecting the mixture to air jet milling to obtain fine powder after collision grinding for a certain period of time; Step S6: preparing a green body: mixing the S5 fine powder with a binder and a solvent, sieving, and then forming and isostatically pressing to obtain a green body; Step S7: heat treatment of the magnet: sintering and secondary aging treatment are performed on the green body obtained in step S6 to obtain the final magnet.
2. A low eddy current loss permanent magnetic material according to claim 1, characterized in that: In the step S1, the total amount of rare earth elements (Pr+Nd+Dy) is between 30 and 33 parts, and Dy is between 0.5 and 2.0 parts, wherein the mass ratio of Pr:Nd is 20:80 or 25:
75.
3. A low eddy current loss permanent magnetic material according to claim 2, characterized in that: In the step S1, the mass fraction of Fe is 60-68 parts; the M element is one or more of copper Cu, manganese Mn, zirconium Zr, gallium Ga and silicon Si, and the mass fraction thereof is 0.5-1 part; the remaining parts of 100 parts are the boron element B component.
4. The low eddy current loss permanent magnetic material according to claim 1, characterized in that: In the step S2, the magnetic powder is refined to a particle size of less than 3.0 μm.
5. The low eddy current loss permanent magnetic material according to claim 1, characterized in that: In step S3, the collaborative grain boundary diffusion treatment material is Tb x Al y Cu z , wherein x accounts for 60-80 parts, y accounts for 15-30 parts, z accounts for 5-10 parts, and the total mass fraction is 100 parts, and the mass percentage of the mixed magnetic powder obtained in step S2 is between 0.3% and 1%, and Tb x Al y Cu z The particle size is controlled at 0.1-0.5 μm; the smelting and casting process is as follows: after the raw materials are prepared, the vacuum system can be stopped when the vacuum degree in the furnace reaches a specified value, and then argon is filled into the furnace and the high-frequency induction current is turned on to start heating. After the alloy is completely melted, it is refined at 1300-1500°C for 3-5 minutes; then the casting system is started, the crucible is slowly poured, and the molten alloy liquid is poured into the tundish. Through the opening of the tundish, the slurry drips uniformly onto the high-speed rotating copper roller, the linear speed of the copper roller surface is controlled to obtain a faster cooling speed, and a casting sheet is obtained after cooling.
6. The low eddy current loss permanent magnetic material according to claim 1, characterized in that: In step S4, hydrogen is injected into the casting environment. A certain amount of hydrogen absorbed by the casting will be removed after hydrogen decomposition is completed, and the remaining hydrogen is retained until the sintering stage in step S6 where it is dehydrogenated together.
7. The low eddy current loss permanent magnetic material according to claim 1, characterized in that: The casting is ground in the air flow mill for 0.5-1.5h. Antioxidants and lubricants are also added in step S5. The weight fractions of lubricants and antioxidants are 0.05-0.12 parts, including 0.03-0.08 parts of antioxidants and 0.02-0.04 parts of lubricants. The rest is the magnetic powder after the above treatment, with a total weight fraction of 100 parts.
8. The low eddy current loss permanent magnetic material according to claim 1, characterized in that: The green embryo forming process in step S6 is to press and form the green embryo in a 2.0-2.5T pulse magnetic field, 180-200MPa isostatic pressure and a green embryo density of 50-60%, and the whole process is carried out in a nitrogen-protected glove box; the dehydrogenation sintering is carried out in a vacuum environment, and after the casting is saturated with hydrogen, the excess hydrogen is evacuated by a vacuum system, and the furnace body is heated to 950°C-1100°C for sintering for 5-10h; after the dehydrogenation sintering is completed, the heating system is turned off to cool the alloy to room temperature with argon gas; In step S6, an adhesive and a solvent are also added, wherein the adhesive is a volatile organic compound and the solvent is gasoline; the mass fractions of the adhesive and the solvent are 0.35-0.6 parts, of which the adhesive is 0.05-0.1 parts and the solvent is 0.3-0.5 parts; the rest is the magnetic powder after the above treatment, and the total mass fraction is 100 parts.
9. The low eddy current loss permanent magnetic material according to claim 1, characterized in that: In step S7, secondary aging treatment is performed, the first tempering heat treatment temperature is 850-950°C, the time is 3-5h, and the second tempering heat treatment temperature is 450°C-650°C, the time is 3-6h, to obtain the final permanent magnet material.
Citation Information
Patent Citations
Neodymium iron boron magnet added with terbium powder and preparation method thereof
CN104575901A
High-performance neodymium-iron-boron magnet and preparation method
CN116741486A
High-performance low-eddy-current-loss neodymium-iron-boron magnet and preparation method thereof
CN118430922A
Method for preparation of permanent magnet
CN1246864C
RFeB BASED SINTERED MAGNET
JP2020013975A